2008
DOI: 10.1021/ar700270t
|View full text |Cite
|
Sign up to set email alerts
|

Ceragenins: Cholic Acid-Based Mimics of Antimicrobial Peptides

Abstract: The prevalence of drug-resistant bacteria drives the quest for new antimicrobials, including those that are not expected to readily engender resistance. One option is to mimic Nature's most ubiquitous means of controlling bacterial growth, antimicrobial peptides, which have evolved over eons. In general, bacteria remain susceptible to these peptides. Human antimicrobial peptides play a central role in innate immunity, and deficiencies in these peptides have been tied to increased rates of infection. However, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
176
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 192 publications
(184 citation statements)
references
References 38 publications
2
176
0
1
Order By: Relevance
“…11 Modified antimicrobial LL-37 peptides, such as FF/CAP18, and a synthetic antimicrobial peptide mimic, ceragenin CSA-13, also have the potential to suppress growth of colon cancer cells. [12][13][14][15] It was found that expression of LL-37 is reduced during progression of stomach cancer from atrophic gastritis to adenocarcinoma. The modified antimicrobial peptide FF/CAP18 exerts antiproliferative effects on the SAS-H1 squamous carcinoma cell line.…”
Section: Introductionmentioning
confidence: 99%
“…11 Modified antimicrobial LL-37 peptides, such as FF/CAP18, and a synthetic antimicrobial peptide mimic, ceragenin CSA-13, also have the potential to suppress growth of colon cancer cells. [12][13][14][15] It was found that expression of LL-37 is reduced during progression of stomach cancer from atrophic gastritis to adenocarcinoma. The modified antimicrobial peptide FF/CAP18 exerts antiproliferative effects on the SAS-H1 squamous carcinoma cell line.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46] Significant membrane activity of CSAs results in bacterial membrane permeabilization and depolarization. 44,47 Previous studies indicate that antimicrobial activity of ceragenins against Gram-negative bacteria is usually lower than the effects against Gram-positive species. The authors suggest that differences in CSA activities are caused by a high content of phosphatidylethanolamine, which might inhibit cationic steroids from binding as well to some bacterial membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, elevated eDNA and NET levels and their accumulation in biological fluids is a factor activating innate immune responses, which considerably affect the development of such diseases as asthma and chronic obstructive pulmonary disease [48], periodontitis [49], antineutrophil cytoplasmic antibody-associated vasculitis (AAV) [29], or cancerassociated thrombosis [50]. Quantitative analysis of the physical chemistry of polyelectrolytes has been useful for designing possible countermeasures to release endogenous antimicrobial peptides trapped in the polyelectrolyte bundles present in purulent fluids [5,45,[51][52][53][54][55][56]. Better penetration through this complex network might be achieved using a nanotechnology approach.…”
Section: Condensation Of Dna By Cationic Peptidesmentioning
confidence: 99%